(untitled) (Journal of the Bangladesh Agricultural University, 2025)
Research was done at the National Goat Research Program, NARC, Bandipur, Tanahun, Nepal with the objective to identify the pattern of live weight changes (kg) and daily weight gain (g/day) of different genetic groups of Boer crosses (Boer 75% and Boer 50% genotypes) and Khari goats from birth to yearling. The live weight of goats at different stages of growth were taken and recorded properly. Five hundred sixty-nine kids for birth weight, 534 kids for weaning weight (3 months), 467 for six-month weight, 320 for nine-month weight, and 279 for twelve-month weight were used in this study. Findings revealed that the body weight of different genetic groups (Boer 75%, Boer 50% and Khari) at birth to nine months, except 3 months was statistically similar (p>0.05) for Boer 50% and Boer 75% blood level, but Boer 75% blood level was significantly (p<0.05) higher body weight at 3 months. In contrast, at twelve months, Boer 50% had significantly (p<0.05) higher body weight than Boer 75%. Khari goat had significantly lower body weight from birth to twelve months in comparison to Boer genetics. Likewise, the mean daily weight gain (MDWG) of different genetics of goats from birth to 3 month was significant (p<0.05) with Boer 75%, having better results of Boer crosses, but it didn’t continue for 3 to 6 months whereas Boer 50% had better performance that tend to continue for 6 to 9 months. Considering MDWG from birth to 12 month, Boer 50% had better results than Boer 75% and Khari genetics. There was no significance difference (p>0.05) in MDWG for birth type and sex of the kids in the three months intervals, but the overall MDWG from birth to 12 months was significant (p<0.05) for sex with male having higher daily weight gain. The interaction of birth type and sex on MDWG of different genetics groups had the significant (p<0.05) effects with Boer 50% having better results. Thus, it can be concluded that while looking at the pattern of live weight change and mean daily weight gain of different genetic groups of Boer crosses and Khari during birth to yearling, Boer 50% proved to be having relatively higher superior performing genetics suggesting need to consider these scientific inferences to develop different nutritional based management plan focusing to Boer 50% cross in achieving higher profit from crossbred goats. J Bangladesh Agril Univ 23(1): 85–92, 2025